2009
DOI: 10.1590/s1678-77572009000700016
|View full text |Cite
|
Sign up to set email alerts
|

The ART approach: clinical aspects reviewed

Abstract: The success of ART as a caries management approach is supported by more than 20 years of scientific evidence. ART follows the contemporary concepts of modern cariology and restorative dentistry. It challenges treatment concepts such as step-wise excavation and the need for complete removal of affected dentine. The ART approach so far has mainly used high-viscosity glass-ionomer as the sealant and restorative material. Cariostatic and remineralization properties have been ascribed to this material which require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…The cost of the more resistant high-viscosity GICs recommended by literature 16 is approximately three times higher than similar GICs manufactured in Brazil. This price difference has a large impact on the development and expansion of oral health to poorer populations at high risk of caries.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The cost of the more resistant high-viscosity GICs recommended by literature 16 is approximately three times higher than similar GICs manufactured in Brazil. This price difference has a large impact on the development and expansion of oral health to poorer populations at high risk of caries.…”
Section: Introductionmentioning
confidence: 94%
“…Specially designed for ART, the high-viscosity GICs have a relatively slow curing and improved mechanical properties compared to low and medium viscosity cements, which has resulted in increased survival of restorations 13 . Recent systematic reviews have shown that the longevity of ART restorations with high-viscosity GICs is similar to the gold standard treatment with amalgam 12,[14][15][16] .…”
Section: Introductionmentioning
confidence: 96%
“…O CIV possui propriedades físicas favoráveis tais como adesão ao esmalte, à dentina e ao metal, além da propriedade anticariogênica pela liberação de íons flúor. Além disso, apresenta coeficiente de expansão térmica semelhante à da estrutura do dente, biocompatibilidade e baixa citotoxidade 1,[3][4][5][6][7]23 .…”
Section: Introdução|unclassified
“…he Atraumatic Restorative Treatment (ART) approach combines the preventive component with the restorative procedure, and has the potential to be minimally invasive and to maximally preserve the tooth structure [1,2,3]. It involves the removal of infected tooth tissues using hand instruments, and the cavity including adjacent pits and fissures is restored using a filling material, usually a glassionomer cement (GIC) [1,3,4].…”
mentioning
confidence: 99%
“…It involves the removal of infected tooth tissues using hand instruments, and the cavity including adjacent pits and fissures is restored using a filling material, usually a glassionomer cement (GIC) [1,3,4].…”
mentioning
confidence: 99%